Finite Element Study on Mechanical Performances of Multi-Span Metal Faced Sandwich Panels under Temperature Actions. Issue 3 (May 2019) - Tang, Zhirong; Zha, Xiaoxiong; Wang, Baolin
Abstract: Metal faced sandwich panel is composed of two relatively high strength metal faces and a relatively thick and lightweight insulated core. Under the continuous action of temperature such as strong sunlight, the multi-span metal faced sandwich panels can be destroyed. In this paper, the finite element (FE) software ABAQUS was used to study the stress and deformation of these sandwich panels under temperature action. The FE results show that the compressive stress in the mid-span region of the metal panel is larger and it gradually decreased from the middle to the two sides. The deformation at the centre of side span of sandwich panels is larger. The support constraints at the bottom of the sandwich panel have a great influence on the temperature stress. The fixed sandwich panel is more likely to occur wrinkle failure than the hinged one. To reduce the effects of temperature, two effective methods are proposed. The method increasing the density of the core material can increase the buckling stress and improve the bearing capacity against temperature action. The other method reducing the length of each segment of the sandwich panel can effectively release the temperature stress and reduce the negative effects of temperature.